Civil society around the Baltic rim: edited on occasion of the 10th Baltic Sea Parliamentarian Conference by order of the Standing Committee of the BSPC - Schleswig-Holsteinisches Institut für Friedenswissenschaften -SCHIFF- an der Universität Kiel (2001)
Abstract: Contents: Hanne-Margret Birckenbach, Christian Wellmann: The making of civil society in the Baltic Sea region: on parliamentary co-operation, Russian participation and multilateralism (4-11); Heinz-Werner Arens: Parliament and civil society: why they should co-operateand how they can do it. The Schleswig-Holstein experiences (12-15); Petter Wille: Civil society and democratic development on the CBSS agenda (16-20); Raymond Stephens: Assisting, advocating, advising: the NGO Centre in Riga (21-23); Eva Maria Hinterhuber: Struggling for human rights in the army: Russia's soldiers' mothers movement (24-28); Ritva Grönick, Laura Päiviö: Pioneering security: the Finnish Committee for European Security (STETE) (29-32); Wolfgang Günther, Antonia Wanner: Founding a family: the environmental NGO-network Coalition Clean Baltic (33-36); Astrid Willer: Towards a Baltic refugee-net: the Refugee Council Schleswig-Holstein (37-41); Hanne-Margret Birckenbach, Christian Wellmann: Kaliningrad: a pilo